Etiology, diagnostics and treatment of the dry eye syndrome - Maguza, Filip (Przewodnik Lekarza/Guide for GPs, 2005)
The essence of dry eye syndrome are pathologic changes in composition, stability and tension of lacrimal film, leading to corneal and conuctival damage, in extreme cases also to lost of vision. The lacrimal film is three-dimensional structure covering the eye surface close to eyelid space. It fulfills the important protection, nutritious and optic function in relation to cornea and conuctivis. It consists of three layers – lipid, hydro and mucose. The symptoms of dry eye syndrome arise as a result of many etiologic factors and appear in various ways in different patients which makes diagnostic extremely difficult. The most patients’ complaints are feeling of foreign body uder the eyelids, itch, conuctival’s bloodshot. In most advanced cases appears photophobia, upset of vision and pain. The basic diagnostic tests in dry eye syndrome are Shrimer’s test, Lipcof, But, fluorescein test. The main form of treating dry eye syndrome is treating with eye drops and gels which imitate the normal lacrimal film and fulfill its protection function in relation to cornea and conuctivis. In difficult cases where conservative treating is insufficient, the surgeon treating is applicable. The main idea of such procedure is to stop lacrimal outflow. The early and correct diagnosis and also appropriate treating of dry eye symptoms, to a large extent prevents from complications and in noticable way decreases ailments connected with this illness.